Front Cover: Amine‐Functionalized Spin Crossover Building Blocks (Eur. J. Inorg. Chem. 43/2019). Issue 43 (13th November 2019) - Flötotto, Henrik; Secker, Tim; Kögerler, Paul; Besson, Claire
Abstract : The Front Cover shows an aluminum sheet painted with thermochromic lacquer based on functionalized derivatives of a traditional spin‐crossover staple, namely iron(II) bis(tris(pyrazolyl)borate) complexes. Facile, controlled pyrazole metathesis allows us to introduce various functional groups, exemplified here by three nitro derivatives. This enables a slew of post‐reactions, ranging from reduction to the corresponding amines to the subsequent introduction of thioether residues, with the perspective of covalently anchoring such complexes to various environments. We thank Dominion Colour Corporation for their support in preparing the experimental lacquer coating. More information can be found in the Communication by P. Kögerler, C. Besson et al. For more on the story behind the cover research, see the Cover Profile.